ANCA Associated Vasculitis and Renal Failure Related to Propylthiouracil and Hyperthyroidism Induced Cholestasis in the Same Case - Mehmet Tuncay; Emine Kivrakoglu; Itir Yegenaga; Erkan Dervisoglu (Case Reports in Nephrology)
Introduction. Liver involvement due to hyperthyroidism and also ANCA positive vasculitis related renal failure cases were reported separately several times before. However, to our knowledge, these two complications together in the same case had never been observed before. Case Presentation. The case of an ANCA positive 71-year-old Caucasian male with renal failure and lung involvement, subclinical hyperthyroidism, and intrahepatic cholestatic jaundice was presented in this paper. After exclusion of all of the other possibilities, cholestatic hepatitis was explained by subclinical hyperthyroidism; renal failure and lung involvement were interpreted as ANCA related vasculitis which might be a side effect of propylthiouracil use. Conclusion. The coexistence of these rare conditions in the same patient deserves emphasis and it is worth reporting. This case demonstrates that following the clinical course of the patient is essential after prescribing any medications to see whether any complication occurs or not. If the complications of this case were noticed earlier, it would be possible to treat and to prevent the permanent damages.